Ibn Juljul's Generations of physicians and sages - Ibn Juljul, Sulayman ibn Hassan. (Leiden ; Boston)
ix, 144 sayfa
Keywords: “In the present book, Oliver Kahl offers, for the first time, a complete, annotated English translation of Ibn Juljul's Tabaqat al-atibba'wa-l-hukama', one of the earliest Arabic texts of its kind. Ibn Juljul's work, completed in the year 987 CE in Córdoba, is essentially a collection of biographical essays on ancient and medieval physicians, scientists and philosophers, interspersed with numerous anecdotes and containing a highly instructive, relatively long section on 'Andalusian sages'. The work represents a most crucial source for our understanding of the evolution and the development of medicine and philosophy in Muslim Spain, drawing also on a number of otherwise unattested Latin-into-Arabic translations, and abounding moreover in burlesque literary embellishments.“ --